Debris development in fretting contacts – Debris particles and debris beds. (September 2020) - Kirk, A.M.; Shipway, P.H.; Sun, W.; Bennett, C.J.
Abstract: In this study, the formation and destruction of compacted beds of oxidized debris particles are investigated. Fretting tests of steel specimens were conducted, employing a cylinder-on-flat geometry with displacement amplitude being varied. The debris was examined, both in the form of the debris beds and in the form of loose debris; together, these were characterized to better understand the mechanisms of debris bed formation and development throughout the fretting process. XRD was employed to determine the phase makeup of the debris, with SEM imaging and particle size analysis employed to understand the evolution of the debris from nanoparticles into agglomerates and then into sintered bed structures. Highlights: Metallic fraction of debris ejected from steel-on-steel fretting tests found to fall with increased applied displacement. Particle size was found to be largely independent of number of fretting cycles, although found to vary with displacement. Ejected debris particles at a range of sizes observed to consist of oxide crystallites on the order of 0.1 μm in diameter.